A Review of Parham’s 4th Edition of The Immune System: A Clear and Clean Immunology TextReview of: <source>The Immune System</source>, <edition>4th ed.</edition>; <person-group> <name name-style="western"><surname>Parham</surname><given-names>Peter</given-names></name></person-group>; ( <year>2014</year>). <publisher-name>Garland Science, Taylor & Francis Group, LLC</publisher-name>, <publisher-loc>New York, NY</publisher-loc>. <fpage>532</fpage> pages. - Cindy Knall (American Society for Microbiology, 2015)
Review of: The Immune System, 4th ed.; Peter Parham; (2014). Garland Science, Taylor & Francis Group, LLC, New York, NY. 532 pages.